COMPARATIVE STUDY OF EOS (EQUATION OF STATES) MODELS FOR FITTING ENERGY VERSUS VOLUME DATA IN THERMODYNAMICS - Bandhaso, David; Lukmantoro, Arif; Sholihun, Sholihun (Prodi Fisika FST UNJA, 2024)
One of the essential aspects of material design research is studying the stability of the model designed. In Thermodynamics, material stability can be expressed by the equation of state (EOS). However, not all EoS will fit with the energy versus volume data from the material being designed. Moreover, if the materials prepared have a unique structure, more factors need to be considered so that the data fitting is carried out more precisely. In this research, a comparative study of 1 mathematical approach (second order polynomial) and 4 EoS (Murnaghan EoS, Birch EoS, Birch EoS, Birch-Murnaghan EoS, and Vinet EoS) was carried out for fitting energy versus volume data on 3D (bulk) and 2D materials. obtained from density functional theory (DFT) calculations. This research found that fitting energy versus volume data in 3D material models can be done using second-order polynomials. In contrast, for 2D models, only two EoS fit (Birch-Murnaghan and Vinet). Apart from that, the result is that the Vinet equation of state is an equation that has the smallest tolerance value in the range of 10-4 - 10-10 eV